Topological Effects and Performance of Dabbawala Graph Model: A Study - Vaidhyanathan, P.; Selvi Vaidhyanathan, V. Thamarai (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2018)
Graph theory is widely applied in Engineering, Computer Science and Business studies. The aim of this research is to throw light on how graph theory could be applied in common real world problems. One such problem that is considered to address in this paper is the working pattern of Dabbawala in Mumbai. The purpose of the paper is two-fold: to propose an innovative model graph model and to attest the proposed graph model in relevance to existing theorems by procuring diversity of results.